Syncope: finding the cause of the drop 1 - Olshansky, Brian (Henry Stewart Talks, 2015)
Syncope: a common problem, Challenge #1: understanding the event, Challenge #2: deciphering the cause, Challenge #3: assessing risk of recurrence & death, Syncope and heart failure
Reviewed at 2021/01/10